Top soil layer equi-electrical conductivity and pollution with salts mapping for a region located within Baghdad city - Baghdad Science Journal (مجلة بغداد للعلوم)
This research deals with the study of top soil electrical conductive regions located within Baghdad City. The research included measuring the dissolved soil material extraction Electrical Conductivity (EC) with an aqueous solution for the top (0-30 cm) soil layer of the study area. As the electrical conductivity values increase by increasing the amount of dissolved salts in principle, we can consider that the aim of this research is to predict the amount and distribution of (soil contamination with salts) which is represented by the (Salt Index), this factor calculated for each soil representative sample taken from the region with a depth of (30 cm). Laboratory (EC) test values measured by the use of solutions (EC) digital meter for the extract of the dissolved soils with a distilled de-ionized water using the ratio of (2:1) .The distributed (EC) values for the field representative soil samples used lately to plot a contour equi-electrical conductivity map and EC soil fluctuation profiles, in which reflected the top soil layer salinity distribution according to Tigris river position in the study area , also it reflects the increase and decrease of this layer salinity in a relation to the river position. This study concluded that the highest soil salinity concentrations located at the southern east part of the study area, while the lowest concentrations are located on the intersection areas with Tigris river stream, other areas in which are few kilometers far from the river stream showed moderate salinity concentrations. These results could be helpful for Environmental and agricultural benefits, through identifying the salty soil pollution region and look for ways of treatment.